2021
DOI: 10.1002/ccr3.4192
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose spinal and opioid‐free anesthesia in patient with Severe Aortic Stenosis and SARS‐CoV‐2 infection: Case report

Abstract: The best anesthesiologic approach to severe AS patient has not been adequately studied in literature. Although the current guidelines have a cautious attitude in this regard, Combined Spinal-Epidural Anesthesia (CSEA) has proved to be a safe technique. Therefore, we would like to provide our experience with a severe AS and COVID-19 patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This resembles the data of our study, where the prevalence of undiagnosed aortic stenosis was 3.4% [ 14 ]. Aortic stenosis and valve disease in general, like other pathologies, define specific and appropriate anesthetic management [ 47 , 48 , 49 ]. Not all valvular pathologies are clinically significant; mild mitral or tricuspid valve diseases need only a change in lifestyle, according to the most recent guidelines [ 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This resembles the data of our study, where the prevalence of undiagnosed aortic stenosis was 3.4% [ 14 ]. Aortic stenosis and valve disease in general, like other pathologies, define specific and appropriate anesthetic management [ 47 , 48 , 49 ]. Not all valvular pathologies are clinically significant; mild mitral or tricuspid valve diseases need only a change in lifestyle, according to the most recent guidelines [ 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…SA, in this case, was not possible due to some absolute contraindications: as to the first patient, a nephropathic subject, NAO therapy was not suspended, therefore blood coagulation framework was compromised; as regards the second patient, it was not possible to proceed with SA due to severe Aortic Stenosis. In the case of Aortic Stenosis, it has been demonstrated that it is still possible to carry out a NA using a Low-Dose Spinal [ 18 ]. This was not possible in our management due to technical difficulties of approach and surgical times.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic stenosis (AS), a fixed cardiac output state, is always a challenge for anesthesiologists as high risk for severe hypotension, ischemic heart disease, and cerebral hypoperfusion should be considered in such patients 1 . Regional anesthesia particularly subarachnoid block is known to be associated with a rapid and massive decline in systemic vascular resistance (SVR) due to potent sympatholysis leading to reduction in venous return, and the patient may not be able to compensate these changes sufficiently due to fixed cardiac output state 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Aortic stenosis (AS), a fixed cardiac output state, is always a challenge for anesthesiologists as high risk for severe hypotension, ischemic heart disease, and cerebral hypoperfusion should be considered in such patients. 1 Regional anesthesia particularly subarachnoid block is known to be associated with a rapid and massive decline in systemic vascular resistance (SVR) due to potent sympatholysis leading to reduction in venous return, and the patient may not be able to compensate these changes sufficiently due to fixed cardiac output state. 2 General anesthesia (GA) can be an option in such patients but may have an even more pronounced cardiovascular effect as compared to neuraxial anesthesia due to an induction‐triggered hypotension with a decrease in venous return and reduced vascular tone in combination with its negative inotropic effect.…”
Section: Introductionmentioning
confidence: 99%